Download as pdf or txt
Download as pdf or txt
You are on page 1of 5

Example 1: Fourier Transform

Consider a sinusoidal signal

𝑥(𝑡) = 3cos⁡(500𝜋𝑡 + 0.1𝜋)

and let us sample it at a frequency 𝐹𝑠 = 2𝑘𝐻𝑧.

i) Determine and expression for the sampled sequence 𝑥[𝑛] = 𝑥(𝑛𝑇𝑠 ) and determine its
Discrete Time Fourier Transform 𝑋(𝜔) = 𝐷𝑇𝐹𝑇{𝑥[𝑛]};

ii) Determine 𝑋(𝐹) = 𝐹𝑇{𝑥(𝑡)};;

iii) Recompute 𝑋(𝜔)⁡from the 𝑋(𝐹)⁡and verify that you obtain the same expression as in a).

Solution

i. We know:
1 1
𝑇𝑠 = =
𝐹𝑠 2000𝐻𝑧
𝑥[𝑛] = 𝑥(𝑡)|𝑡=𝑛𝑇𝑠 = 3cos⁡(500𝜋𝑛𝑇𝑠 + 0.1𝜋)
Substituting for 𝑇𝑠
1
𝑥[𝑛] = 𝑥(𝑡)|𝑡=𝑛𝑇𝑠 = 3cos⁡(500𝜋𝑛 + 0.1𝜋)
1000

𝑥[𝑛] = 𝑥(𝑡)|𝑡=𝑛𝑇𝑠 = 3cos⁡(0.5𝜋𝑛 + 0.1𝜋). Equivalently, using complex exponentials,


𝑥[𝑛] = 1.5𝑒 𝑗0.5𝜋𝑛 + 1.5𝑒 −𝑗0.1𝜋 𝑒 −𝑗0.5𝜋𝑛

This is from the fact that cos(0.5𝜋𝑛𝑇𝑠 + 0.1𝜋) = ⁡ 𝑒 𝑗0.1𝜋 𝑒 𝑗0.5𝜋𝑛 + 𝑒 −𝑗0.1𝜋 𝑒 −𝑗0.5𝜋𝑛

Therefore 3𝑐𝑜𝑠(0.5𝜋𝑛𝑇𝑠 + 0.1𝜋) = 3𝑒 𝑗0.1𝜋 𝑒 𝑗0.5𝜋𝑛 + 3𝑒 −𝑗0.1𝜋 𝑒 −𝑗0.5𝜋𝑛

Therefore, its DTFT becomes


𝜋 𝜋
𝑋(𝜔) = 𝐷𝑇𝐹𝑇{𝑥[𝑛]} = 3𝜋𝑒 𝑗0.1𝜋 𝛿 (𝜔 − 2 ) + 3𝜋𝑒 −𝑗0.1𝜋 𝛿(𝜔 + 2 )
𝜋
Because: 𝑒 𝑗0.5𝜋𝑛 = ⁡ 𝑒 𝑗𝑛𝜋/2 which is equivalent to a unit impulse delay 𝜔 by 2

with −𝜋 < 𝜔 < 𝜋

ii.
Since
𝐹𝑇{𝑒 𝑗2𝜋𝐹𝑜𝑡 } = 𝛿(𝐹 − 𝐹0 )
Then

𝑋(𝐹) = 1.5𝑒 𝑗0.1𝜋 𝛿(𝐹 − 500) + 1.5𝑒 −𝑗0.1𝜋 𝛿(𝐹 + 500) for all F.

iii.

Recall that 𝑋(𝜔) = 𝐷𝑇𝐹𝑇{𝑥[𝑛]} and 𝑋(𝐹) = 𝐹𝑇{𝑥(𝑡)} are related as


+∞

𝑋(𝜔) = 𝐹𝑠 ∑ 𝑋(𝐹 − 𝑘𝐹𝑠 )|𝐹=𝜔𝐹𝑆 /2𝜋


𝑘=−∞
With 𝐹𝑠 the sampling frequency. In this case there is no aliasing, since all frequencies are
𝐹𝑠
contained within = 1𝑘𝐻𝑧. Therefore, in the interval −𝜋 < 𝜔 < +𝜋 we can write
2
𝑋(𝜔) = 𝐹𝑠 𝑋(𝐹)|𝐹=𝜔𝐹𝑆 /2𝜋
With 𝐹𝑠 = 2000𝐻𝑧. Substitute for X(F) from part (b) to obtain
𝜔 𝜔
𝑋(𝜔) = 2000(1.5𝑒 𝑗0.1𝜋 𝛿 (2000 − 500) + 1.5𝑒 −𝑗0.1𝜋 𝛿 (2000 + 500))
2𝜋 2𝜋
Now using the property of the ‘delta’ function for any constant 𝑎 ≠ 0,
1 𝑡
𝛿(𝑎𝑡) = 𝛿( )
|𝑎| 𝑎
Therefore
𝜋 𝜋
𝑋(𝜔) = 3𝜋𝑒 𝑗0.1𝜋 𝛿 (𝜔 − ) + 3𝜋𝑒 −𝑗0.1𝜋 𝛿(𝜔 + )
2 2
which is same as in (b).

Example 2: Difference equation.

Consider the following system:

Here, the system F is defined by the input-output relationship


𝐹{𝑧[𝑛]} = 𝑧[𝑛] − 𝑧[𝑛 − 1],
And ∆ is the unit delay
∆{𝜔[𝑛]} = 𝑧[𝑛] − 𝑧[𝑛 − 1]
Now,
𝑧[𝑛] = 2𝑥[𝑛] − ∆{𝑦[𝑛]} = 2𝑥[𝑛] − 𝑦[𝑛 − 1].
Therefore, substituting the expression for z[n] into the first equation, we can write:
𝑦[𝑛] = 𝑧[𝑛] − 𝑧[𝑛 − 1]
=⏟(2𝑥[𝑛] − 𝑦[𝑛 − 1]) − ⏟ (2𝑥[𝑛 − 1) − 𝑦[𝑛 − 2]
=𝑧[𝑛] =𝑧[𝑛−1]
= 2𝑥[𝑛] − 𝑦[𝑛 − 1] − 2[𝑛 − 2] = 2𝑥[𝑛] − 2𝑥[𝑛 − 1]

Example 3, on convolution

Compute the convolution of the following two signals and plot the result on the set
of axes provided. Show all your work!
Example 4: Sampling

Solution

You might also like